KONDISI TERUMBU KARANG DI PERAIRAN LIUKANG TANGAYA KABUPATEN PANGKAJENE DAN KEPULAUAN - Iwan Nurhidayat; Rustam Rustam; Abdul Rauf (Jurnal Pendidikan Teknologi Pertanian, 2019)
Coral reef is one of the most important ecosystem in marine environment. With high biodiversity and productivity as one of their characteristic makes coral reef value in nature regulation cannot be replaced. This study held from July until October 2018. The aim of this study is to understand coral reefs in Liukang Tangaya waters. Data collection using Underwater Photo Transect method. The result are, from 15 observation station show that coral reefs in Liukang Tangaya in damaged condition with average of live coral is 18.91% with the main cause come from destructive fishing.